Replacing yellow maize with Illipe nut (Shorea stenoptera) improves growth performance and meat quality of porker pigs - Evelyn, L.L.L.; Abu Daud, N.H.; Loh, T.C.; Candyrine, S.C.L. (Springer Science and Business Media B.V., 2024)
The effects of incorporating Illipe nut into the diet of pigs, in replacement of yellow maize, on their growth performance and meat quality was investigated in a 60 days feeding trial. Twenty-four male pigs were divided into two treatments and fed diets with 0% (T1) or 15% (T2) Illipe nut inclusion. Feed intake, live weight (LW) and backfat thickness (BFT) were taken and used to calculate average daily feed intake (ADFI), average daily gain (ADG), feed conversion ratio (FCR) and increase in backfat (IBF). At the end of the trial, final LW and BFT were measured. Pigs were then slaughtered and hot carcass weight (HCW), pH45mins, pH24hrs and dressing percentage (DP) were determined. Other analysis, including total moisture, thawing loss (TL), cooking loss (CL) and water holding capacity (WHC), were conducted on pork samples. Nutritional content and fatty acid (FA) composition of pork samples were analyzed, and nutritional indices were calculated. Improvements (P < 0.05) in final LW, ADG, final BFT, IBF and FCR were seen in pigs fed the T2 diet. Additionally, the T2 pork was superior (P < 0.05) in HCW, DP, pH24hrs, TL, CL, total moisture and WHC than T1 pork. The FA composition of T2 pork was also improved, with a higher (P < 0.05) PUFA:SFA ratio, indicating lower SFA and higher PUFA levels than T1 pork. Along with this, T2 pork had lower (P < 0.05) index of atheroginicity (IA) and higher (health promoting index) HPI levels, indicating that the T2 pork is a healthier choice for consumption. These findings indicate that the inclusion of 15% Illipe nut into the diet of porker pigs improved their overall growth performance and meat quality.